LAW ENFORCEMENT OF DESTRUCTIVE FISHING IN INDONESIAN SEAS - Ook Mufrohim; Joko Setiyono (UNISSULA, 2020)
Indonesia is a country consisting of many islands. This makes Indonesia rich in natural marine resources consisting of marine products such as fish and other marine animals. Catching fish by means of damage or (destructive fishing) using trawlers, fish bombs, fish anesthesia needs special attention in terms of law enforcement, to support the protection of marine ecosystems and enforcement of existing regulations. This study uses a qualitative method with a normative juridical approach. This research shows weaknesses in committing destructive fishing crimes. This is intended so that law enforcers can enforce according to the provisions of the statutory regulations that are willing, and seek additional personnel or carry out strategies so that they can carry out surveillance in the Indonesian sea from catching fish in destructive ways.